Post-Sekularisme Dan Urgensi Agama Resurektif (Perspektif Pastoral Gereja Katolik) - Benediktus Denar (Jurnal Alternatif Wacana Ilmiah Interkultural, 2017)
The emergence of the post-secular phenomenon as a critique of secularism is not without problem. The revival of religious zeal which is merely restorative in nature without being based on the defense of humanity and the integrity of creation is a great hole that deserves to be criticized from post-secularism. The true post-secularism must present the face of a resurrection religion; sensitive to human anxiety and suffering. The Catholic Church can displays the face of the merciful religion if it can applies pastoral from below and prioritizes the poor and oppressed people. In addition, the apparatus of the Church must show exemplary behavior by abstaining from corrupt